From Therapeutic Relationships to Transitional Care : A Theoretical and Practical Roadmap - Forchuk, Cheryl (Routledge, 2021)
This text provides a foundational understanding of therapeutic relationships and the transitional discharge model (TDM), a person-centered, evidence-based model that supports a smooth transition from hospital to community for people with mental illness Starting with background into the ground-breaking work of Dr. Hildegard Peplau, the mother of modern psychiatric nursing, and moving towards a transdisciplinary transitional discharge perspective, chapters introduce students and practitioners to theoretical, historical, and current perspectives on therapeutic relationships as they relate to transitional care. These perspectives foreground empirical research and practical applications that can be implemented in hospital and community settings. The Appendix features an essential "TDM toolkit" with forms, learning topics, and checklists developed by programs that implement TDM. Essential reading for those studying psychiatric nursing, this book combines theory, research, and best practices into a "roadmap" for students across nursing and psychiatric disciplines to coordinate these systems without having to implement radical changes to practice.
Transitional Discharge Model: Program Information Brochure Example 6. Transitional Discharge Planning - Information for Clients - EXAMPLE Copyright Acknowledgements
OCLC-licensed vendor bibliographic record.
Keywords: Mental health services; Nursing care plans; MEDICAL / Nursing / General; MEDICAL / Nursing / Home & Community Care; MEDICAL / Nursing / Mental Health